Perceived Work Uncertainty and Creativity During the COVID-19 Pandemic: The Roles of Zhongyong and Creative Self-Efficacy - Tang, Chaoying; Ma, Huijuan; Naumann, Stefanie E.; Xing, Ziwei (Frontiers in Psychology, 2020)
Research on the relationship between work stress and employee creativity has been mixed. This study on 823 female attorneys in China identifies employee creative self-efficacy and employees’ value of Zhongyong as moderators in this relationship. In this study, work stress is assessed by the perceived work uncertainty brought on by the COVID-19 pandemic. Our study found that although Zhongyong, which involves an employee’s ambidextrous thinking, can be helpful for employee creativity, low levels of Zhongyong are better for employee creativity in an uncertain context such as the COVID-19 pandemic, due to the fact that high levels of Zhongyong result in an overemphasis on compromise and giving in when times are uncertain. Instead, low levels of Zhongyong will decrease employees’ concern about others’ acceptance in an uncertain environment. In addition, creative self-efficacy motivates employees to engage in creative efforts during times of work uncertainty. In sum, this study found that employee perceived work uncertainty brought on by COVID-19 enhances employee creativity when an employee’s value of Zhongyong is low and creative self-efficacy is high.